Surgical treatment of advanced thyroid cancer invading the trachea, A case presentation and review of literature - Davary H (Tehran University Medical Journal, 1999)
Differentiated carcinoma of the thyroid occruing within the gland is generally not regarded as an aggressive tumor; however, when the tumor extends beyond the gland's capsule and onto adjacent structures, its prognosis worsens. During the past three decades such locally invasive thyroid cancer has been studied, specifically concerning invasion into the airway. Progress in tracheal operations in the past 20 years has changed remarkably in terms of the operative methods and indications for thyroid carcinoma invading the trachea. Resection and primary reconstruction of the trachea invaded by carcinoma of the thyroid should be done in the absence of extensive metastases when technically, feasible. It offers prolonged palliation, avoidance of suffocation and an opportunity for cure. In carefully selected patient with massive regional involvement, radical excision laryngopharyngoesophagectomy and mediastinal tracheostomy is also appropriate. In this article, management of one patient with intraluminal involvement of trachea by thyroid carcinoma is presented and management of upper aerodigestive tract invasion by thyroid cancer reviewed.